Nilai Ikonik: Packaging pada â€œAngkot Gaulâ€ Kota Padang - Masful, Mila Falma (Jurnal Studi Komunikasi, 2017)
Today, there are many advanced transportation tools developed and created by humans in order to meet all the elements of satisfaction in the human self itself. As in Indonesia itself recently will be built rapid train from Jakarta to the city of Bandung. This is one of the qualified facilities that are expected to fulfill the needs of the society in transportation. But behind it all there are some means of transportation where people are not too interested in all sophistication of technology, but has an artistic, iconic and unique value to use. "Angkot Gaul", so the people of Padang City call it and by the drivers make this transport not only deliver passengers to the destination but has a good point of view to use. Like the car modification, Angkot Gaul is known not only in the city of Padang but also national. So with the uniqueness owned Angkot Gaul is eventually used as a packaging that can increase sales of services well and of course the value of satisfaction both by the driver himself and passengers. What is the iconic value and uniqueness of this public transport? The researcher is looking at the meaning of semiotics using the theory of Charles Sanders Pierce which contained the value of semiotics that contained its meaning on Angkot Gaul Padang City in terms of language, color, music and stickers modified by the driver of Angkot Gaul.